A Short Executive Function Training Program Improves Preschoolers’ Working Memory - Blakey, Emma; Carroll, Daniel J. (Frontiers in Psychology, 2015)
Cognitive training has been shown to improve executive functions in middle childhood and adulthood. However, fewer studies have targeted the preschool years – a time when executive functions undergo rapid development. The present study tested the effects of a short four session executive function training program in 54 four-year-olds. The training group significantly improved their working memory from pre-training relative to an active control group. Notably, this effect extended to a task sharing few surface features with the trained tasks, and continued to be apparent three months later. In addition, the benefits of training extended to a measure of mathematical reasoning three months later, indicating that training executive functions during the preschool years has the potential to convey benefits that are both long-lasting and wide-ranging.